2021
DOI: 10.1002/mbo3.1162
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of viral infections between the eastern honey bee (Apis cerana) and the western honey bee (Apis mellifera)

Abstract: It is a widespread practice in China to keep colonies of both the western honey bee, Apis mellifera , and the eastern honey bee, Apis cerana , in close proximity. However, this practice increases opportunities for spillover of parasites and pathogens between the two host bee species, impacting spatial and temporal patterns in the occurrence and prevalence of the viruses that adversely affect bee health. We conducted a 1‐year large‐scale survey to assess the current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 45 publications
3
12
0
Order By: Relevance
“…The cumulative abundance had a different trend, as it gradually increased monthly to peak in July when a decrease proceeded to reach a minimum in October. These results are in line with the seasonal pattern the same pathogens show in the A. mellifera colonies, where they often peak in spring/summer with a possible return in the late season (Tentcheva et al, 2004;D'Alvise et al, 2019;Dalmon et al, 2019b;Loeza-Concha et al, 2020;Chen et al, 2021).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The cumulative abundance had a different trend, as it gradually increased monthly to peak in July when a decrease proceeded to reach a minimum in October. These results are in line with the seasonal pattern the same pathogens show in the A. mellifera colonies, where they often peak in spring/summer with a possible return in the late season (Tentcheva et al, 2004;D'Alvise et al, 2019;Dalmon et al, 2019b;Loeza-Concha et al, 2020;Chen et al, 2021).…”
Section: Discussionsupporting
confidence: 88%
“…That increase may be associated with both the development of the honey bee colonies and the availability of floral resources. Indeed, after the winter, the colony starts the growth of its population, which is intended to peak in summer, with an increased probability both of intra-colonial ( Smith et al., 2013 ; Steinhauer et al., 2018 ; D’Alvise et al., 2019 ; Chen et al., 2021 ) and interspecific environmental transmission ( Bartlett et al., 2019 ; Wilfert, 2021 ). Furthermore, the reduced flower availability in summer prompts pollinators to concentrate on the limited resources available, increasing the probability of pathogen exchanges among the potential host species.…”
Section: Discussionmentioning
confidence: 99%
“…This study provides a molecular basis on a Chinese isolate of BQCV and helps us understand the genomic characteristics of this virus, as well as viral pathogenic mechanism. Previous results also showed that multiple infections were common in A. mellifera and A. cerana in China [9, 47, 48]. More importantly, it provides a possible way to characterize the infection dynamics of BQCV to avoid several viruses are co-infected within one bee.…”
Section: Discussionmentioning
confidence: 92%
“…One mite species in particular, Varroa destructor (Anderson and Trueman), has drawn the attention of scientists owing to its tremendous effects on a key pollinator: the western honey bee (Apis mellifera) [15]. Varroa destructor is an ectoparasite of both its original host Apis cerana and the sister species A. mellifera and is well-known to act as a vector of several viruses [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%